c - e (b, 2013)
On cooperative movement in Indian subcontinent with reference to the views of Rabindranath Tagore, 1861-1941, Bengali author, Prafulla Chandra Ray, 1861-1941, Bengali chemist and Akhter Hameed Khan, social scientist, on cooperation.
Includes bibliographical references (page 213).
In Bengali; includes passages in English.
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Political and social views; Ray, Prafulla Chandra, -- 1861-1944 -- Political and social views; Khan, Akhter Hameed; Cooperation -- South Asia